PENEGAKAN HUKUM SYARAT MUTLAK MEWUJUDKAN NEGARA HUKUM DAN TUJUAN NEGARA (PENELITIAN PENEGAKAN HUKUM LALULINTAS JALAN DI KAWASAN SENEN) - Muchtar B Pakpahan (to-ra, 2017)
Abstract A country of law requires the existence of law enforcement, in this case the goal is just for well being and the protection of citizens rights, protecting all the regions, as well giving a guarantee to each of these members of the community to impose their daily activities, it has a legal state laws, there is a body of justice that free and impartial, having basic laws, providing education, maintainning discipline on society, provide the security to any members of the community for activities every single day include in the convenience on the road, such as: pleasantness of pedestrians orderlines the user of motorcyles, distraction from vendors, the protection an area of the sidewalk from vendors, the side of the road users as parking spaces, The discipline user on the road, the obediance of pedestrian for using overpass, if all these things happened then must be law enforcement, especially operationalising the traffic of law in transportation roadway by the sipport of the technology and the officers who disciplines. Keywords: penegakan hukum syarat untuk negara hukum